2016
DOI: 10.1590/1980-5373-mr-2015-0705
|View full text |Cite
|
Sign up to set email alerts
|

Combustibility and reactivity of coal blends and charcoal fines aiming use in ironmaking

Abstract: The selected fuels for this study were three typical PCI coals of different ranks and origins identified as A (Colombian), B (Russian), and C (Australian), and Brazilian charcoal fines from wood carbonization, named as CC. These samples were prepared by quartering and crushing according to ASTM D 2013-03 13. Characterization was performed by proximate analysis (ABNT NBR 8289 14 , NBR 8290 15 and NBR 8293 16), ultimate analysis (ASTM D 5373-08 17), gross

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
5
0
3
Order By: Relevance
“…Com isso, é possível operar o alto-forno com uma temperatura de chama menor do que quando se utilizam materiais com menor teor de hidrogênio. Em contraste, o hidrogênio causa uma degradação prematura do coque no alto-forno, danificando a permeabilidade através da formação de finos dentro do reator [11].…”
Section: Resultsunclassified
“…Com isso, é possível operar o alto-forno com uma temperatura de chama menor do que quando se utilizam materiais com menor teor de hidrogênio. Em contraste, o hidrogênio causa uma degradação prematura do coque no alto-forno, danificando a permeabilidade através da formação de finos dentro do reator [11].…”
Section: Resultsunclassified
“…A Tabela 1 mostra os resultados da análise química imediata, elementar e poder calorífico para a casca de sementes da moringa oleifera e para o carvão mineral. [7] . Este tipo de material é desejado para altas taxas de injeção, devido o curto tempo de permanência deste material na zona de combustão do altoforno.…”
Section: Resultsunclassified
“…According to previous studies, charcoal’s CO 2 reactivity is much higher than metallurgical coke. ,− It is believed that the high porosity and surface area of biocarbon are the contributing factors. ,, Kaffash et al observed that the CO 2 reactivity of all charcoals decreased during the process of increased densification. This decline in reactivity was likely attributed to the reduction in porosity caused by densification.…”
Section: Metallurgical Properties Of Biocarbonsmentioning
confidence: 99%